Evolving the world's most dangerous animal. Issue 2 (February 2015) - Weetman, David; Clarkson, Christopher S.
<x xml:space="preserve">Abstract</x> The devastating consequences of malaria are well known but many mysteries remain about its key protagonists, a handful of Anopheles species. New work provides a framework for solving such puzzles, by generation and analysis of whole genome assemblies for 16 Anopheles species, with genomic flexibility a key emergent theme.